Contrasting patterns of genetic and phenotypic divergence of two sympatric congeners, Phragmites australis and P. hirsuta, in heterogeneous habitats - Qiu, Tian; Liu, Zhiyuan; Li, Haiyan; Yang, Ji; Liu, Bao; Yang, Yunfei (Frontiers in Plant Science, 2023)
Habitat heterogeneity leads to genome-wide differentiation and morphological and ecological differentiation, which will progress along the speciation continuum, eventually leading to speciation. Phragmites hirsuta and Phragmites australis are sympatric congeners that coexist in saline-alkaline meadow soil (SAS) and sandy soil (SS) habitats of the Songnen Meadow. The results provided genetic evidence for two separate species of reeds. Genetic diversity and spatial genetic structure supported the specialist-generalist variation hypothesis (SGVH) in these two sympatric reed species, suggesting that P. australis is a generalist and P. hirsuta is a habitat specialist. When we compared these different species with respect to phenotypic and genetic variation patterns in different habitats, we found that the phenotypic differentiation of P. australis between the two habitats was higher than that of P. hirsuta. Multiple subtle differences in morphology, genetic background, and habitat use collectively contribute to ecological success for similar congeners. This study provided evidence of the two reed congeners, which should contribute to their success in harsh environments.